Viral hepatitis B and C: similarities and difference - M. S. Karyagina; E. Yu. Plotnikova; E. N. Baranova; O. A. Vorosova; M. A. Shamray; S. F. Zinchuk; K. A. Krasnov (Лечащий Врач, 2021)
The article presents data on the main features typical for viral hepatitis B and C, describes differences in the structure of viruses, extra-hepatic clinical manifestations, mechanisms for the development of hepatocellular carcinoma, considers new data on antiviral therapy and vaccination. The data of the original study of patients with chronic hepatitis B and C, in whom we assessed the function of the biliary tract, vegetative status and vegetative reactivity, content of tissue magnesium and zinc, are also given.